Micro-plastics as a new challenge in water resource management; Various forms and removal methods, (A review study) - Mahdi Asadi-Ghalhari; Amin Kishipour; Roqiyeh Mostafaloo; Yalda Arast (Pizhūhish dar Bihdāsht-i Muḥīṭ., 2020)
Background and Purpose: Today, the production of plastic materials has multiplied with the growth of population and the development of industry in the world. Micro-plastics are released into the environment by the decomposition of plastic materials. The World Health Organization (WHO) has called these particles emerging pollutants due to their highly durable and bioaccumulative. The present study reviews the characteristics, health hazards, values, as well as the efficiency of different methods of eliminating micro-plastics in aquatic environments. Materials and Methods: In this review study, the keywords Micro-plastic, Water-drinking, Pollution, and Removal were searched and studied in articles from 2000 to 2020 published by Pubmed, Google scholar, Science direct, and Scopus. Results: Studies show that in addition to the food chain, this pollutant is also present in bottled drinking water, which can affect human health, the environment and living organisms in aquatic environments. conclusion: It is suggested that more studies be done on this pollutant in aquatic environments, especially in Iran. In addition, educate people about less use of plastic in everyday life, teach them how to recycle properly, and get help from the industry to provide a suitable alternative to plastic. Article type: A review article.